Primary Pancreatic Lymphoma Masquerading as Carcinoma - Nasser A. N. Alzerwi (Case Reports in Oncological Medicine)
Adenocarcinoma is the most common primary pancreatic neoplasm type, followed by secondary pancreatic lymphoma and primary pancreatic lymphoma (PPL). PPL is associated with peripancreatic lymphadenopathy and usually presents as a homogenous mass with extrapancreatic invasion into surrounding structures. However, localized involvement of the distal pancreas is uncommon, and diffuse involvement of the pancreas is even rarer. Herein, we present the case of a 53-year-old woman with PPL of the uncinate process with biliary obstruction mimicking pancreatic adenocarcinoma, successfully diagnosed nonoperatively. Abdominal computed tomography showed an ill-defined uncinate process mass, hypodense with mild enhancement (3.9×3.4×3.5 cm), infiltrating the second and third parts of the duodenum. Biopsy revealed NHL with no evidence of adenocarcinoma. PPL was diagnosed. She received chemotherapy with a CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone) protocol with rituximab, which she tolerated with no clinical or radiological evidence of recurrence at 1-year follow-up.